Crop response to simulated diflufenican carryover and sprayer contamination with a diflufenican premixture - Woolard, Matthew C.; Norsworthy, Jason K.; Barber, L. Tom; Roberts, Trenton L.; Thrash, Benjamin C.; Piveta, Leonard B.; Godar, Amar S. (Frontiers in Agronomy, 2025)
Palmer amaranth [Amaranthus palmeri (S.) Wats] has evolved resistance to nine sites of action (SOAs) globally, leaving producers searching for effective herbicide options. Bayer CropScience has announced intentions to launch a series of Convintro™ brand herbicides, one of which will be a premixture including diflufenican, metribuzin, and flufenacet for preemergence use in soybean [Glycine max (L.) Merr]. Diflufenican is a WSSA group 12 herbicide that would add a new SOA for soybean producers. With the anticipated launch of the premixture, research is needed to evaluate the potential for diflufenican carryover or tank contamination from a diflufenican premixture to injure corn, cotton, grain sorghum, rice, and soybean. Carryover experiments were conducted in 2022 and 2023 in Fayetteville, AR, and near Stuttgart, AR. Diflufenican was applied preplant at 0, 7.5, 15, 30, 60, and 120 g ai ha-1, with crops being planted after a 1.3 cm irrigation or rainfall event occurred. Injury was <10% for rice and corn, <5% for grain sorghum, and no crop response from cotton at 14 days after emergence (DAE). No detrimental effect was observed on various crops by 28 DAE. Additionally, tank contamination experiments were conducted in Arkansas in Fayetteville, near Stuttgart, near Colt, and in Keiser. A 0.17:0.35:0.48 ratio of a diflufenican:metribuzin:flufenacet premixture, at rates up to 103 g ai ha-1, was applied at the 3-leaf growth stage for each crop. Injury was ≤30% for cotton (Gossypium hirsutum L.), <20% for corn (Zea mays L.) and soybean, and <5% for grain sorghum (Sorghum bicolor L.) and rice (Oryza sativa L.) at 7 days after treatment (DAT). By 28 DAT, injury was <15% for cotton, <10% injury for soybean and rice, and no crop response for corn or grain sorghum. Overall, the potential for diflufenican carryover or risk of injury from sprayer contamination appears low, with no yield reductions occurring in any of the evaluated crops in either set of experiments.